Protease nexin-1 deficiency increases mouse hindlimb neovascularisation following ischemia and accelerates femoral artery perfusion - Selbonne, Sonia (Sci Rep, 2021)
We previously identified the inhibitory serpin protease nexin-1 (PN-1) as an important player of the angiogenic balance with anti-angiogenic activity in physiological conditions. In the present study, we aimed to determine the role of PN-1 on pathological angiogenesis and particularly in response to ischemia, in the mouse model induced by femoral artery ligation. In wild-type (WT) muscle, we observed an upregulation of PN-1 mRNA and protein after ischemia. Angiography analysis showed that femoral artery perfusion was more rapidly restored in PN-1(−/−) mice than in WT mice. Moreover, immunohistochemistry showed that capillary density increased following ischemia to a greater extent in PN-1(−/−) than in WT muscles. Moreover, leukocyte recruitment and IL-6 and MCP-1 levels were also increased in PN-1(−/−) mice compared to WT after ischemia. This increase was accompanied by a higher overexpression of the growth factor midkine, known to promote leukocyte trafficking and to modulate expression of proinflammatory cytokines. Our results thus suggest that the higher expression of midkine observed in PN-1- deficient mice can increase leukocyte recruitment in response to higher levels of MCP-1, finally driving neoangiogenesis. Thus, PN-1 can limit neovascularisation in pathological conditions, including post-ischemic reperfusion of the lower limbs.